2022
DOI: 10.1111/1365-2435.14070
|View full text |Cite
|
Sign up to set email alerts
|

Feedbacks between size and density determine rapid eco‐phenotypic dynamics

Abstract: 1. Body size is a fundamental trait linked to many ecological processes-from individuals to ecosystems. Although the effects of body size on metabolism are well-known, the potential reciprocal effects of body size and density are less clear. Specifically, (a) whether changes in body size or density more strongly influence the other and (b) whether coupled rapid changes in body size and density are due to plasticity, rapid evolutionary change or a combination of both.2. Here, we address these two issues by expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 94 publications
3
16
0
Order By: Relevance
“…Previous studies showed that predator–prey body size ratios significantly influence temperature and nutrients effects [19,61] and that body size responds to changes in nutrients, temperature and ecological dynamics in specific ways [18]. A recent study showed that the body size of a species can affect its own ecological dynamics [41], which we have also shown here as tight coupling between the phenotypic and ecological dynamics of Euplotes sp . (figure 5).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Previous studies showed that predator–prey body size ratios significantly influence temperature and nutrients effects [19,61] and that body size responds to changes in nutrients, temperature and ecological dynamics in specific ways [18]. A recent study showed that the body size of a species can affect its own ecological dynamics [41], which we have also shown here as tight coupling between the phenotypic and ecological dynamics of Euplotes sp . (figure 5).…”
Section: Discussionsupporting
confidence: 75%
“…To understand the mechanisms through which temperature and nutrients affected the observed food web dynamics, we quantified the reciprocal effects of ecological dynamics and body size on each other using convergent cross mapping (CCM) [52]. The CCM algorithm has now been used multiple times across ecological systems and taxa reliably to estimate the strength of causal effects between variables for which time-series are available [41,[53][54][55][56][57][58] and we followed this specialized literature to infer causation in our data (see electronic supplementary material, appendix II figure S1-S15). Concisely, CCM quantifies the strength of causation of one dynamical variable onto another by measuring the extent to which the time series of one variable can reliably estimate the state of another variable [52].…”
Section: (E) Quantifying Top-down/bottom-up Effects and Ecophenotypic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in protist shape and size have multiple ecological consequences, including population dynamics and ecological interactions within communities (33, 41, 85), as well as total respiration, which decreases with volume (86). Shifts in size and shape can occur quite rapidly and can be as dramatic as 50% or more (61, 87). Likely, species that cannot rapidly respond to temperatures are thus replaced by those that can, leading to high species turnover (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in energy availability at the base of the microbial food web should also result in (Fig. 1C): 1) an increase in protist volume in response to more energy availability, 2) an increase in aspect-ratio as increased available energy releases cells from shape metabolic constraints, 3) an increase in sigma-intensity, due to increased production of cellular machinery to process available energy, and, 4) an increase in autotrophy (i.e., decrease in the red/green ratio of cells) relative to heterotrophy (42, 61, 62). We show that warming and CO 2 have significant, negative interactive effects, on the taxonomic and functional composition of peatland protist communities, which has important consequences for C cycling in these systems.…”
Section: Introductionmentioning
confidence: 99%